Relationship between household behaviour during pandemic and impact of excessive plastic waste to the environment among Malaysians / Nik Nursyuhada Nik Ahmad Ramzan and Siti Nurul Mawadhah Paiman - Nik Ahmad Ramzan, Nik Nursyuhada; Paiman, Siti Nurul Mawadhah (2022)
Due to the fact that plastics take thousands of years to decompose, there is an accumulation of plastic waste especially in the landfill. In order to address the issue influencing households in Malaysia to change their behaviour during the pandemic, excessive plastic waste has to be studied. The use of plastic during the pandemic rose with the rising usage of single use plastic. This study aims to identify the correlation of household behaviour to plastic waste during the COVID-19 pandemic and the consequences of excessive plastic waste on the environment among Malaysians. This study focuses on household behaviour, excessive usage of single-use plastic and mismanagement on the disposal of plastic. The sample size for this study will contain 384 respondents which are among the Malaysian households. This study will use quantitative survey and cross-sectional study. The data from respondents will be gathered via the questionnaire. The results show that there is a significant relationship between excessive usage of single-use plastics and plastic waste pollution. Therefore, government interventions, environmental education and implementation of regulations to solve plastic waste pollution need to be strictly done.